2015
DOI: 10.1039/c5ra16114b
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of CeO2 nanoparticle sensitized CdS nanorod photocatalyst with improved visible-light photocatalytic degradation of rhodamine B

Abstract: A heterostructure photocatalyst consisting of one-dimensional (1D) CdS nanorods (NRs) and cerium dioxide (CeO2) nanoparticles (NPs) was successfully synthesized via a solvothermal method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 46 publications
(51 reference statements)
3
35
1
Order By: Relevance
“…However, it was decreased significantly when the IPA was introduced. This confirms that the hydroxyl radicals are the main active species for the photocatalytic degradation of Congo red …”
Section: Resultssupporting
confidence: 72%
“…However, it was decreased significantly when the IPA was introduced. This confirms that the hydroxyl radicals are the main active species for the photocatalytic degradation of Congo red …”
Section: Resultssupporting
confidence: 72%
“…Here, benzoquinone (BQ) was introduced as scavenger for • O 2 − , AgNO 3 for e − , EDTA for h + , and tertiary butanol (TBA) for • OH in the solution [22,26,[28][29][30][31].…”
Section: Photocurrent and Photocatalytic Activity Measurementsmentioning
confidence: 99%
“…Lee et al found that the H 2 evolution rate over core-shell structured CdS@TiO 2 increased nearly 6 times compared with bulk CdS [24]. Alternatively, CeO 2 is also a suitable coupler used to improve the photocatalytic activity of CdS because the redox couple Ce 4+ /Ce 3+ in CeO 2 can effectively separate the photogenerated electrons and holes [25,26]. For example, Tang's group found that the conversion rate of nitroaromatics over CdS@CeO 2 nanowires was more than twice as much as that of blank CdS nanowires under visible light irradiation [25].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[11] Such aremarkable HER activity without any co-catalyst suggests ah igh mobility and low recombination rate of charge carriers in these compounds. [13] Among the Cd 2 P 3 Xc ompounds,C d 2 P 3 Cl exhibits as ignificantly higher activity than Cd 2 P 3 Br and Cd 2 P 3 I( Figure S17). Cd 7 P 4 Cl 6 and Cd 4 P 2 Cl 3 exhibit significantly higher HER activity than the CdS-and TiO 2based photocatalysts under visible-light irradiation.…”
mentioning
confidence: 98%